Sofrimento, responsabilização e desejo: uma análise dos processos decorrentes das mudanças de moradia no âmbito do Programa Vila Viva Belo Horizonte - Luana Dias Motta (2013)
In 2004, the municipal administration of Belo Horizonte launched the Vila Viva Program, a set of integrated actions aiming at the urbanization, social development and regularization of slums and villages. Nowadays, Vila Viva is the largest urbanization program in the country and it works within a logic that recognizes the slums as established settlement in the city. Although it seems at first sight pointless to problematize this Program I considered it important to ask the question: what means, especially for local dwellers, do not eradicate the slum? Following this question, this research analyzes how Vila Viva, its logic and purposes are structured, revealing that the Program is closely related to the mechanisms of biopower, a power which has life as its object and objective. In order to understand how these mechanisms of power work along the implementation of such policy of inclusion in the city and how they are experienced by local dwellers, I conducted interviews with people removed from their homes and resettled in Vila Vivas apartments in Aglomerado da Serra, one of the biggest slums in Belo Horizonte. The residents´ narratives about this process are marked by feelings of sorrow and longing as well as positive assertions about the change. Hence, ambiguity pervades how Vila Viva is experienced by residents. However, contrary to what I expected to find there, the feelings of sorrow and logging were not related to direct coercion but to the modulation of desires and conducts. In other words, the construction of an alignment between the government of the other and the government of the self was what made possible the compliance of dwellers to the Program, despite their feelings of sorrow and longing for leaving their old houses, their neighbors and their livelihood. If, on the one hand, having the desire and the subjectivity as the center of these practices of government helps to perpetuate the suffering, as the dwellers are made responsible for the inadequacy of apartments and its problems, on the other hand, this means that the government of the self does not adjust perfectly to the government of the other, as it is shown by the non-expected and prohibited practices in the new buildings.